Wavelet characterizations for investigating nonlinear oscillators - Mohd Aftar Abu Bakar,; Noratiqah Mohd Ariff,; Metcalfe, Andrew V.; Green, David A. (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study investigates the wavelet-based system identification capabilities on determining the system nonlinearity based on the system impulse response function. Wavelet estimates of the instantaneous envelopes and instantaneous frequency are used to plot the system backbone curve. This wavelet estimate is then used to estimate the values of the parameter for the system. Two weakly nonlinear oscillators, which are the Duffing and the Van der Pol oscillators, have been analyzed using this wavelet approach. A case study based on a model of an oscillating flap wave energy converter (OFWEC) was also discussed in this study. Based on the results, it was shown that this technique is recommended for nonlinear system identification provided the impulse response of the system can be captured. This technique is also suitable when the system’s form is unknown and for estimating the instantaneous frequency even when the impulse responses were polluted with noise.